Trajectories of rural teachers, from their narratives - Pinilla Benítez, Pedro Martín; Ávila Garzón, Liliana Inés (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The article presents the results of the research Trajectories of rural teachers, narratives from the Escuela Nueva Model in Pauna, Boyacá. The objective was to recognize and analyze the experiences of four rural teachers, through their narratives on the Escuela Nueva model, in order to learn about their practices and knowledge. Through narratives and interviews, pedagogical practices were made visible in a context unknown by governments, institutions and society. A qualitative approach was used, based on a type of narrative biographical research, since teachers discover in their professional experiences reflections that have allowed them to redefine their work with rural communities. The results allow recognizing the teachers' trajectories from three main axes: 1) experience, life and cultural environments of new school teachers; 2) the meanings and knowledge of teachers in the rural context from academic and administrative components; 3) the desires, dilemmas and expectations of rural teachers. It is concluded that teaching practices in rural contexts transcend what is established in the Escuela Nueva model.